Gambaran Lemak Tubuh dan Tingkat Kebugaran Jasmani pada Atlet Bulu Tangkis Remaja Putri KONI Jawa Barat Tahun 2023 - Audhrey Tyara Mizard; Ieva Baniasih Akbar; Umar Islami (Bandung Conference Series: Medical Science, 2024)
Abstract. Badminton is a sport that is very popular in Indonesia. Physical fitness and body fat are important indicators for athletes to pay attention to. The aim of this research is to determine the description of body fat and physical fitness levels in young female badminton athletes at KONI West Java in 2023. The method of this research is analytical research with a cross sectional design. Thirty-three female youth badminton athletes from KONI West Java aged 11-17 years were research subjects using a non-probability sampling method with a total sampling technique. Body fat percentage is measured with the BIA test. Physical fitness is measured using the bleep test method. This research shows that female youth badminton athletes KONI West Java have an average body fat of 23.16% (moderate). KONI West Java female youth badminton athletes have an average physical fitness level of 46.23 ml/kg/min (excellent). Based on this research, it is hoped that it can show a picture of body fat and physical fitness so that KONI West Java female youth badminton athletes can pay attention to body fat percentage and physical fitness levels to improve the athletes' performance & achievements. Physical fitness can also be influenced by other factors such as nutritional intake, lifestyle and exercise. Abstrak. Bulu tangkis merupakan salah satu cabang olahraga yang sangat digemari di Indonesia. Kebugaran jasmani dan lemak tubuh merupakan indikator yang penting untuk diperhatikan bagi para atlet. Tujuan penelitian ini adalah mengetahui gambaran lemak tubuh dan tingkat kebugaran jasmani pada atlet bulu tangkis remaja putri KONI Jawa Barat Tahun 2023. Metode penelitian ini adalah penelitian analitik dengan desain cross sectional. Tiga puluh tiga atlet bulu tangkis remaja putri KONI Jawa Barat usia 11-17 tahun menjadi subjek penelitian menggunakan metode non-probability sampling dengan teknik total sampling. Persentase lemak tubuh diukur dengan BIA test. Kebugaran jasmani diukur dengan metode bleep test. Penelitian ini menunjukkan bahwa atlet bulu tangkis remaja putri KONI Jawa Barat memiliki lemak tubuh dengan rata-rata yaitu 23,16% (moderate). Atlet bulu tangkis remaja putri KONI Jawa Barat memiliki tingkat kebugaran jasmani dengan rata-rata yaitu 46,23 ml/kg/min (excellent). Berdasarkan penelitian ini, diharapkan dapat memperlihatkan gambaran lemak tubuh dan kebugaran jasmani sehingga atlet bulu tangkis remaja putri KONI Jawa Barat dapat memperhatikan persentase lemak tubuh dan tingkat kebugaran jasmani untuk meningkatkan kinerja & prestasi para atlet. Kebugaran jasmani juga dapat dipengaruhi oleh faktor lain seperti asupan gizi, gaya hidup, serta latihan.